2021
DOI: 10.1016/j.heliyon.2021.e08034
|View full text |Cite
|
Sign up to set email alerts
|

Possible potentials of curcumin for pregnancies complicated by intra-uterine growth restriction: role of inflammation, angiogenesis, and oxidative stress

Abstract: Objectives So far, various etiologies have been stated for Intra-uterine growth restriction (IUGR) with a wide variety of pathways involved in their pathogenesis. Among these pathways, impaired angiogenesis, inflammation, and oxidative stress are among the most important ones. Curcumin has raised notable attention due to its anti-inflammatory and antioxidant activity in different in-vitro studies and clinical trials. The present study aimed to investigate the possible po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Many etiological factors have been identified in the pathogenesis of FGR, encompassing various pathways (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Among the most significant are inflammation, inadequate angiogenesis, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many etiological factors have been identified in the pathogenesis of FGR, encompassing various pathways (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Among the most significant are inflammation, inadequate angiogenesis, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous inflammatory and proinflammatory markers, including monocytes, neutrophils, MPO, IL6, IL1, IL10, have been studied in FGR. In addition to elevated leukocyte and monocyte levels, neutrophil/monocyte-derived substances have been found to be increased in FGR (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin is a polyphenol, characterized by the inclusion of two aromatic rings, and its phenolic hydrogens are responsible for its ability to react with reactive species and are believed to impart antioxidant activity to the molecule (88). So far, data from in vivo and in vitro studies have shown the antioxidant activity of curcumin in different pathological conditions through different pathways (89,90). The antioxidant activity of curcumin mainly from two aspects: one is curcumin as a free radical scavenger (91,92); and the other is curcumin as inducers of antioxidant signaling pathways in cells, by enhancing the activity of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and phase II metabolizing enzymes, heme oxygenase (HO-1) and quinone oxidoreductase (NQO1) (33,67,93,94).…”
Section: Curcumin and Intestinal Antioxidant Function Of Intrauterine...mentioning
confidence: 99%